Highly Efficient and Robust Full‐Color Organic Afterglow through 2D Superlattices Embedment. Issue 44 (30th September 2022) - Zhang, Jingyu; Xu, Shen; Zhang, Longyan; Wang, Xin; Bian, Yanfang; Tang, Senlin; Zhang, Runqi; Tao, Ye; Huang, Wei; Chen, Runfeng
Abstract: Purely organic afterglow (POA) originating from the slow radiative decay of stabilized triplet excited states has shown amazing potential in many fields. However, achieving highly stable POA with high phosphorescent quantum yield (PhQY) and long lifetime is still a formidable challenge owing to the intrinsically active and sensitive nature of triplet excitons. Here, triplet excitons of phosphors are protected and stabilized by embedding in tricomponent trihapto self‐assembled 2D hydrogen‐bonded superlattices, which not only enables deep‐blue POA with high PhQY (up to 65%), ultralong lifetime (over 1300 ms) and the highest figure‐of‐merit at room temperature, but also achieves excellent stability capable of resisting quenching effects of oxygen, solvent, pressure, light, and heat. In addition, the POA color is tuned from deep‐blue to red via efficient Förster resonance energy transfer from the deep‐blue POA emitters to the fluorophores. Moreover, with the high‐performance, robust, and full‐color POA materials, flexible anti‐counterfeit displays and direct‐current (DC)‐driven lifetime‐encrypted color Morse Code applications are facilely realized. Abstract : An efficient and universal strategy is proposed to prepare high‐performance and robust organic afterglow with high figures‐of‐merit by 2D hydrogen‐bonded superlattices embedment of phosphors. Deep‐blue organic afterglow with high efficiency up to 65%, ultralong lifetime over 1300 ms, and robust emission that can resist the quenching effects from oxygen, solvent, stress, and heat is achieved.